A Modified Technique for Induced Gingival Growth Around Compromised Teeth Prior to Implant Placement: A Report of Two Cases - Saade, Jorge; Bassani, Marcelo; Castro, Andre; Saade, Esther Gomes [UNESP]; Zen, Bruno Massucato; dos Santos, Mateus Bertolini Fernandes; Maior, Bruno Sotto; Francischone, Carlos Eduardo (Quintessence Publishing, 2022)
Regenerative and reconstructive periodontal plastic surgery are important options for treating marginal tissue recession and can be indicated for root coverage or periodontal procedures prior to implant placement. Among the available procedures, periodontal flaps with subepithelial connective tissue graft (CTG) is the most common treatment option to achieve proper tissue manipulation. The present study proposes a modification of a previous technique for inducing spontaneous gingival growth around teeth that will be extracted prior to implant placement, through successive reduction of the buccal root surface. This successive reduction of root surfaces is performed with diamond burs, and such reductions create space for the gingival tissue to grow coronally by reducing root convexity and, consequently, stimulating the healing process with the formation of granulation tissue that will then differentiate into keratinized tissue. The presented technique is suggested to improve the esthetic outcomes for cases involving tooth extraction, implant placement in the extraction socket, and immediate loading with interim restoration and CTG.